Design of a 843MHz 35µW SAW oscillator using device and circuit co-design technique - Zhu, Yao (2013)
This paper presents a 35μW SAW oscillator operating at 843MHz. The low power consumption is achieved through the co-design of SAW resonator and oscillator circuit with the aid of an accurate equivalent circuit model of SAW resonator. The equivalent circuit model of SAW resonator is improved from idealized lumped circuit model by accurate extraction and derivation of design parameters from FEM simulation in ANSYS. The simulated phase noise is -139.8dBc/Hz at 100KHz offset.